ChemInform Abstract: Palladium‐Catalyzed Reduction of Acid Chlorides to Aldehydes with Hydrosilanes. Issue 4 (31st January 2013) - Fujihara, Tetsuaki; Cong, Cong; Iwai, Tomohiro; Terao, Jun; Tsuji, Yasushi
Abstract A mixture of a palladium precursor and a phosphine ligand shows high catalytic activity in the reduction of acid chlorides to aldehydes with hydrosilanes.